The Spatial Formation of The Berastagi Sub District, Kabupaten Karo - Wendi Prayudi (International Journal of Architecture and Urbanism, 2020)
Berastagi sub-district is located in the Karo district of North Sumatra province. The majority of people in the Berastagi sub-district are the Karo tribe. The space arrangement settlement is very inspired by grade local culture, makes this area have traditional characteristics. Besides grade culture is very impressive, Berastagi is also be known as a tourism place. In the expected research, settlement can be well-identified it can be was found the spatial formation so that the development of the area will be carried out to be adapted with public expectation. So as the expansion expected can improve the standard of available living in term convenience, harmony and safety to serve life routinely.